Intelligence, Financial Literacy, and Financial Behavior: A Study on Generation Z - Ningtyas, Mega Noerman; Putra, Rafli Sahrian (Fakultas Ekonomi, UIN Maliki Malang, 2024)
Financial behavior plays an important role in determining individual welfare. A person will behave financially well when he understands the concept of finance well. In addition, each individual is also endowed with intelligence to help him in carrying out every activity that will be carried out. The purpose of this study is to examine the role of financial literacy on financial behavior in Generation Z and also to examine intelligence as a moderating role. The analysis used was the SEM-PLS approach. We collected 400 respondents using an online questionnaire. The results of this study indicate that financial literacy has a positive effect on financial behavior and intelligence has a positive impact on financial behavior. However, intelligence cannot strengthen the influence between financial literacy and financial behavior. The financial behavior of Gen Z needs to get more attention from the government considering that Indonesia is now entering the demographic bonus era where this generation dominates the overall population.